Business English writing skills : a writing survival kit - Byrne, Timothy, ....- (Leuven : Acco, 2014)
So far, not a single book has been published grouping the various written genres that businesspeople need in their jobs on a daily basis. Students of business English writing skills are often provided with a rather unsystematic compilation of information from heterogeneous sources. The result has been unsatisfactory, both for lecturers and learners. This book tries to fill that niche. The units have been selected on the basis of real feedback from students doing placements in companies. Genuine information from student error analysis has been added. The book can be used in class, as selfstudy, but also as quick reference for businesspeople, when they have to produce a particular genre and wonder, "How is this done again?" For each unit, a sample is shown and analyzed; the user is then asked to emulate the model in the form of a number of applications and exercises. Sample answers are provided on the website. The level aimed at is B2-C1
Keywords: Handelscorrespondentie